Reduced Circulating Levels of miR-491-5p and miR-485-3p Are Associated with the Occurrence of Vertebral Fractures in Postmenopausal Women with Osteoporosis. (7th March 2022) - Xu, Jixi; Li, Mingbo; Pei, Wei; Ding, Jinyong; Pan, Yueran; Peng, Huifeng; Lin, Shiman; Huang, Yanbo
Abstract : Objective. Postmenopausal women experiences osteoporotic structural damage and bone fragility resulting from reduced bone formation and increased bone resorption. Osteoporosis frequently affects the vertebral column and causes compression fractures. This study aims to characterize roles of miRNAs in osteoporosis and subsequent incidence risk of vertebral fractures for postmenopausal women. Methods. Differentially expressed miRNAs between osteoporotic patients with vertebral fractures and osteoporotic patients without fracture were identified. This retrospective study included 78 osteoporotic patients with vertebral fractures and 82 osteoporotic patients without vertebral fractures. The plasma levels of bone metabolic markers, 25-hydroxyvitamin D (25-(OH)VitD), propeptide of type I procollagen (PINP), and β-Carboxyl terminal peptide (β-CTx), were detected using the patented electro-chemiluminescence (ECLIA) method. The expression levels of miR-491-5p and miR-485-3p were determined by qRT-PCR. Pearson correlation analysis was carried out to assess the relationship between miR-491-5p, miR-485-3p, and bone metabolic markers. Receiver operating characteristic (ROC) curves and the area under the ROC curve (AUC) were used to evaluate the performance of miR-491-5p and miR-485-3p in diagnosing the occurrence of vertebral fractures in osteoporotic patients.Results: The plasma levels of PINP and β-CTx were elevated but the plasma level of 25-(OH)VitD was declined in osteoporotic patients with vertebral fractures when comparable to those without (< 0.05). The plasma expression levels of miR-491-5p and miR-485-3p were declined osteoporotic patients with vertebral fractures when comparable to those without (< 0.001). Pearson correlation analysis revealed that the relative expression level of miR-491-5p was negatively correlated with the level of 25-(OH)VitD (r = -0.518, < 0.001) but positively correlated with the levels of PINP (r = 0.547, < 0.001) and β-CTx (r = 0.380,  < 0.001). We also observed a negative correlation between the relative expression level of miR-485-3p and 25-(OH)VitD (r = -0.388, < 0.001), a positive correlation between miR-485-3p and PINP (r = 0.422, < 0.001). ROC curves for prediction of vertebral fracture following osteoporosis in postmenopausal women by miR-491-5p expression yielded 0.866 AUC and by miR-485-3p expression produced 0.848 AUC. Conclusion . The data suggest that downregulated expressions of miR-491-5p and miR-485-3p may be involved in the occurrence of vertebral fractures in postmenopausal women with osteoporosis.